Enhanced arsenate removal by lanthanum and nano–magnetite composite incorporated palm shell waste–based activated carbon - Jais, F.M.; Ibrahim, S.; Yoon, Y.; Jang, M. (Elsevier, 2016)
Palm shell waste–based activated carbon (PSAC) was magnetized via hydrothermal impregnation of nano–magnetite, and further coated by various amounts of lanthanum (La) followed by calcination. Numerous batch tests were carried out to observe arsenate removal by La–impregnated, magnetized PSAC (MPSAC–La) in aqueous phase. Isotherm data showed that MPSAC–La(0.36) (weight ratio of La to Fe = 0.36) gave the highest adsorption capacity (227.6 mg g−1), which was approximately 16.5 and 1.6 times higher than PSAC and magnetized PSAC (MPSAC), respectively. As an indication of sorption affinity, MPSAC–La(0.36) had the highest Langmuir constant (KL), which was approximately 230 times greater than that of MPSAC. Based on the pH effect and speciation modeling, arsenate was predominantly removed by precipitation at pH < 8, while it complexed on the surface of La(OH)3 at pH > 8. Lesser La dissolution resulted, owing to a strong binding effect of nano–magnetite with La. XRD, FTIR, SEM–EDS, and N2 gas isotherms showed that the coating of nano–magnetite introduced substantial clogging in the micropores of PSAC, but increased meso– and macropores. However, lanthanum oxide/hydroxide (LO/LH) glued the spaces of nano–magnetite to eliminate most pore structures, and effectively removed arsenate as LaAsO4 at pH 6. Overall, MPSAC–La(0.36) is considered a competitive granular material due to its extremely high sorption capabilities, easy magnetic separation and high regeneration rate.